An evolutionary model for the V404 Cyg system - Bartolomeo Koninckx, Leandro (2023)
V404 Cyg is a low mass X-Ray binary (LMXB) system that has undergone outbursts in 1938, 1989, and 2015. During these events, it has been possible to make determinations for the relevant data of the system. This data include the mass of the compact object (i.e., a black hole; BH) and its companion, the orbital period, the companion spectral type, and luminosity class. Remarkably, the companion star has a metallicity value that is appreciably higher than solar. All these data allow for the construction of theoretical models to account for its structure, determine its initial configuration, and predict its fate. Assuming that the BH is already formed when the primary star reaches the zero age main sequence, we used our binary evolution code for this purpose. We find that the current characteristics of the system are nicely accounted for by a model with initial masses of 9 M· for the BH, 1.5 M· for the companion star and an initial orbital period of 1.5 d, while also considering that at most 30% of the mass transferred by the donor is accreted by the BH. The metallicity of the donor for our best fit is Z=0.028 (twice solar metallicity). We also studied the evolution of the BH spin parameter, assuming that is not rotating initially. Remarkably, the spin of the BHs in our models is far from reaching the available observational determination. This may indicate that the BH in V404 Cyg was initially spinning, a result that may be relevant for understanding the formation BHs in the context of LMXB systems.